Economic Feasibility of Agrivoltaic Systems for Sustainable Small Scale Farming - Juli Burden; Tai McClellan Maaz; Makena Coffman; Ngonidzashe Chirinda; Sunday A. Leonard; Michael Kantar (Food and Energy Security)
ABSTRACT The global push toward renewable energy systems has prompted a desire to more efficiently use land through the co‐location of agricultural and industrial activities. Agrivoltaic systems (AV), crops grown underneath/adjacent to solar photovoltaic (PV) panels, present a unique value proposition to produce food and energy in a single location. Here, we conducted a field trial within a PV site, empirically testing AV methods using small‐scale sustainable farming practices in a peri‐urban landscape in Hawaiʻi. By mimicking commercial production conditions, we identified the most profitable lettuce genotype (e.g., Magenta) and created an enterprise budget to generate realistic financial expectations for those (company, municipality, university) aiming to create energy‐generating foodscapes. These empirical data generated in a commercial setting can be used as valuable inputs for future planning work in a range of different geographies.